PENGARUH KONTEN BERITA COVID-19 DALAM MEDIA REPUBLIKA.CO.ID TERHADAP ADOPSI PERILAKU PROTOKOL KESEHATAN (SURVEI PADA MAHASISWA UPNVJ) - Andreas Pranata Hutauruk, (2021)
The media plays an important role in disseminating information, especially during the current covid-19 pandemic, where information such as health protocols is important for the public to know. The purpose of this study was to find out how much influence the covid-19 news content in the Republika.co.id media had on the adoption of the health protocol behavior of upnvj students. The method in this study uses an explanatory quantitative approach using data from survey results. The population in this study were students of the Jakarta Veterans National Development University, amounting to 12,521 people. The theory in this study uses the theory of information diffusion (innovation). News content is based on three (3) dimensions, namely, Consequences, Timeliness, Factual, while Behavioral adoption is based on five (5) dimensions, namely, Awareness, Interest, Evaluation, Trial, and Adoption. The results of the correlation test are known to have a strong relationship. The results of the influence test are known to have a significant effect. The results of the calculation of the hypothesis with t count can be rejected and Ha accepted, which is applied to the theory used by information diffusion (innovation) where information about health protocols which is an innovation is conveyed through Republika online media. co.id received by UPN Veterans Jakarta students and the significant influence of the covid-19 news content in the Republika.co.id media on the adoption of health protocol behavior for UPN Veterans Jakarta students.